Mothers, mothering, and sport : experiences, representations, resistances - Battaglia, Judy; Bromwich, Rebecca; Redela, Pamela, 1975- (Demeter Press, 2018)
"Mothers and mothering have been a longtime focus of research and study in various academic disciplines, and common topics of interest in mainstream press and popular culture, yet the experiences of mothers and mothering in the area of sport have been less explored. This innovative, interdisciplinary collection provides a space for exploration of the complex dimensions of intersections between mothers, mothering, and sport, as athletes, players, participants, parents and discursive figures. Topics discussed are wide-ranging, from motherwork in sport, mothers as athletes, the athlete mother in sports, representations and expectations of motherhood and health, legal regulation of sports and parenting, as well as sexuality and gender in sports and gaming."--